Influence of different sera on maturation of sheep oocytes in vitro* - REDDY, S M; SHANKARAPPA, T H (The Indian Journal of Animal Sciences, 2012)
Sheep follicular oocytes were collected from ovaries after their slaughter and cultured in vitro by supplementation of fetal calf serum (FCS), Steers serum (SS) or estrous cow serum, day-1 (ECS, d-1) @ 10% of the in Vitro maturation (IVM) media, and the rates of maturation of oocytes in IVM media containing different sera were assessed and compared with their culture in TCM 199 without supplementing serum or hormones.The highest rate of maturation of oocytes were observed when medium was supplemented with ECS d-1 (83.82±1.17%) followed by steers serum (73.33±2.01%), FCS (64.81±1.98%) and medium alone (45.95±2.06).